Chimeric antigen receptor T cells applied to solid tumors - Zhou, Zhongguo; Tao, Can; Li, Jianting; Tang, Johnny Cheuk-on; Chan, Albert Sun-chi; Zhou, Yuanyuan (Frontiers in Immunology, 2022)
Chimeric antigen receptor T cell (CAR-T) therapy is novel tumor immunotherapy that enables autologous T to express synthetic receptors to specifically recognize the surface tumor-associated antigens for exerting subsequent antitumor effects and eliminating the resistance, metastases, and recurrence of cancer. Although CAR T cells have exhibited success in eradicating hematologic malignancies, their applications to solid tumors has not yet been achieved due to obstacles such as the immune-suppressor tumor microenvironment and lack of tumor specific target antigens. In this review, we presented advancements in the development of CAR T cell therapy in solid tumors and offered a brief summary of the challenges, as well as novel engineering and pharmaceutical interventions to overcome these barriers. Looking forward, we discussed the latest studies which are expected to reach the clinicals in the next few years, including CRISPR screens-based CAR modification and CAR T cells driven from progenitor-like T cells. Collectively, this review may inspire researchers and clinicians to develop clinical available strategies of CAR T cell therapies in solid tumor.